A Profile of Patients With Traumatic Brain Injury Within Home Care, Long-Term Care, Complex Continuing Care, and Institutional Mental Health Settings in a Publicly Insured Population. Issue 6 (November 2015) - Colantonio, Angela; Hsueh, Jayden; Petgrave, Josian; Hirdes, John P.; Berg, Katherine
Abstract : Objective: To describe the sociodemographic and clinical profile of people with traumatic brain injury (TBI) in home care, nursing homes, and complex continuing care settings in a national sample. Methods: Cross-sectional study using available Resident Assessment Instrument (RAI 2.0 and RAI Home Care [HC]) national databases in Canada from 1996 to 2011. The profile of people with TBI was compared with patients with and without prespecified neurological conditions within each setting. Participants: Adults 18 years and older identified with TBI ( n = 10 878) and adult patients with other neurological ( n = 422 300) and nonneurological ( n = 571 567) conditions. Main Measures: Demographic and clinical characteristics, functional characteristics, mood and behavior, and treatment and medication variables. Data from Canadian home care (RAI-HC), mental health (RAI-MH), nursing home, and complex continuing care facilities (RAI Minimum Data Set 2.0). Results: Patients with TBI were significantly different on almost all items. They were among the youngest in care settings, and psychotropic drug use by this population was among the highest in at least 2 settings. Conclusion: These data can inform the planning for appropriate care and resources for patients with TBI in a range of settings. Abstract : Supplemental Digital Content is Available in the Text.